Stress Method for Pre-Sowing Stimulation of Seeds and Determination of Their Bioenergy Capacity by Calorimetry - Vasylenkov , Viktor; Gudzenko, Maxim (Science and Innovation, 2024)
Introduction. To date, many different devices and methods have been developed for pre-sowing stimulation of seeds in order to increase yields and to maximize the seed bioenergy capacity. Problem Statement. However, the conventional methods for pre-sowing stimulation of seeds with subsequent determination of germination require a wide range of equipment and consumables plus long research time. Developing new methods of pre-sowing treatment and the development of new methods for determining the bioenergy capacity of sowing material is a promising field of research. Purpose. The purpose of this research is to study the stress method for pre-sowing stimulation of seeds and determination of its bioenergy capacity by the calorimetry method. Materials and Methods. To determine the bioenergy capacity of seed material, two batches of Myronivska-808 variety wheat seeds are taken, one of which is subjected to a stress in the form of impact on a rigid surface. The bioenergy capacity of the seed has been determined with the use of the calorimetric device B-08 M, according to DSTU ISO 1928:2006. Results. It has been shown that the bioenergy capacity before and after impact is 10842 kJ/kg and 12649 kJ/kg, respectively, the difference between them is 1807 kJ/kg. This indicates that as a result of the stress treatment of the seeds, their bioenergy capacity increases by 14.3%. At the same time, no seed damages caused by falling of the seed mass from a height of 3 m on a motionless surface have been found. Conclusions. An increase in the bioenergy capacity of seeds after impact by 14—15% indicates that the stress method of pre-sowing stimulation is rather effective. The use of calorimetry methods may be recommended as a way to control the quality of the stress method of pre-sowing stimulation of seed material.